2017
DOI: 10.1177/1010539517717020
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Commune Health Stations in Chi Linh District, Hai Duong Province, for Prevention and Control of Noncommunicable Diseases

Abstract: The primary health care system in Vietnam has been playing an important role in prevention and control of diseases. This study aimed to describe the capacity of commune health stations in Chi Linh district, Hai Duong province for prevention and control of noncommunicable diseases (NCDs). A mixed-methods (quantitative and qualitative approaches) approach was applied to collect data in 20 commune health stations. The participants, including health workers, stakeholders, and patients with NCDs, were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Thi et al studied all CHCs in one district and concluded that healthcare workers were unqualified to provide screening, diagnosis, and treatments of NCDs. 24 Our study also found that CHC utilization was statistically significantly different among the study provinces, with the total mean number of visits lower in the mountainous region. However, because we do not have the total number of people in each CHC, we cannot make a meaningful comparison of clinical utilization rates.…”
Section: Discussionsupporting
confidence: 59%
“…Thi et al studied all CHCs in one district and concluded that healthcare workers were unqualified to provide screening, diagnosis, and treatments of NCDs. 24 Our study also found that CHC utilization was statistically significantly different among the study provinces, with the total mean number of visits lower in the mountainous region. However, because we do not have the total number of people in each CHC, we cannot make a meaningful comparison of clinical utilization rates.…”
Section: Discussionsupporting
confidence: 59%
“… 34 Limited public financial/budgetary support has also been identified as a major barrier to NCD services in primary healthcare in Vietnam. 45 47 A national-level health worker in Vietnam conveyed the following to Kien et al in 2018:…”
Section: Resultsmentioning
confidence: 99%
“… 41 Furthermore, a lack of interaction between private and public providers and stakeholders was reported for NCD prevention/management activities in Vietnam. 45 A mixed-method study found that Vietnam’s nationally targeted NCD management and control programme lacked L&G capacity. 47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations